Reproducible Ala-Gly oligomerization catalyzed by the natural Borate colemanite in prebiotic conditions - Isabella Rimoldi; Giorgio Facchetti; Lucia Feni; Giacomo Diego Gatta; Paolo Lotti; Silvia Rizzato; Michael S. Christodoulou; Lucia Silvestrini; Leonardo Lo Presti (Scientific Reports)
Abstract The abiogenesis of complex peptides is a yet unsolved problem concerning the origin of life, as it is unclear how specific amino acid sequences could be formed in the absence of a regulation mechanism. Crystalline minerals could have provided template scaffolds to sustain replicable oligomerization processes. We demonstrate that the natural organophilic borate colemanite, CaB3O4(OH)3·H2O, fosters consistent Gly-Ala oligomerization into AG8, G7AG and G7GA strands with well-defined primary sequence (8%, 47% and 45% respectively) from activated glycine and alanine as N-carboxyanhydrides. These Gly-rich sequences are mechanically flexible and may have played a pivotal structural role in driving amino acid loops in ancient polypeptides. In fact, they occur repeatedly in proteins that exploit either structural or transport functions, which belong to ancestral organisms, including Cyanobacteria and Thermoproteota. Our results demonstrate that the consistent synthesis of short well-defined amino acid sequences is possible in a few days of incubation under mild conditions in a prebiotically plausible environment.